Advanced Magnetic Nanostructures - Sellmyer, D.J.; Skomski, Ralph; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2006)
Advanced Magnetic Nanostructures is devoted to the fabrication, characterization, experimental investigation, theoretical understanding, and utilization of advanced magnetic nanostructures. Focus is on various types of 'bottom-up' and 'top-down' artificial nanostructures, as contrasted to naturally occurring magnetic nanostructures, such as iron-oxide inclusions in magnetic rocks, and to structures such as perfect thin films. Chapter 1 is an introduction into some basic concepts, such as the definitions of basic magnetic quantities. Chapters 2-4 are devoted to the theory of magnetic nanostructures, Chapter 5 deals with the characterization of the structures, and Chapters 6-10 are devoted to specific systems. Applications of advanced magnetic nanostructures are discussed in Chapters11-15 and, finally, the appendix lists and briefly discusses magnetic properties of typical starting materials. Industrial and academic researchers in magnetism and related areas such as nanotechnology, materials science, and theoretical solid-state physics will find this book a valuable resource.
Spin-Polarized Electronic Structure -- Nanomagnetic Models -- Nanomagnetic Simulations -- Nanoscale Structural and Magnetic Characterization Using Electron Microscopy -- Molecular Nanomagnets -- Magnetic Nanoparticles -- Cluster-Assembled Nanocomposites -- Self-Assembled Nanomagnets -- Patterned Nanomagnetic Films -- Media for Extremely High Density Recording -- Hard-Magnetic Nanostructures -- Soft Magnetic Nanostructures and Applications -- Nanostructures for Spin Electronics -- Nanobiomagnetics.
Keywords: Magnetism; Magnetic materials; Nanotechnology; Metals; Electronics; Microelectronics; Magnetism, Magnetic Materials; Nanotechnology; Metallic Materials; Electronics and Microelectronics, Instrumentation